La utilización del modelado como alternativa para fortalecer la creatividad de los niños y niñas del nivel inicial 2, paralelo a de la escuela Julio María Matovelle de la ciudad de Loja, en el período 2014-2015 - Cumbicos Espinoza, Juana Rocio (2017)
The present research is determined by THE USE OF MODELING AS A ALTERNATIVE TO STRENGTHEN THE CREATIVITY OF CHILDREN OF THE INITIAL LEVEL 2, PARALLEL "A" OF THE JULIO MARÍA MATOVELLE SCHOOL OF THE CITY OF SHOP, IN THE PERIOD 2014-2015 , In which it was proposed as a general objective to analyze the use of modeling as an alternative to strengthen the creativity of children in the initial level 2, parallel "A" of the Julio María Matovelle School in the city of Loja, in the 2014-2015 period. The type of study that was carried out was descriptive and correlational in which the following methods were used descriptive, analytical, deductive and inductive. Within the techniques were handled the observation and the modeling workshop of plasticine and masses. As instruments a test and post-test was applied to diagnose the problem and verify the application of the modeling. The population with which they worked was 11 children and 6 girls corresponding to the ages of 4 years. In whose research, to the apply the test is found that the 88% of those children are placed in a level half of creativity and the 12% is was in a level low, constituting is in a great problem. However after applying the workshop, was very significant results since implementing the pos-test to verify the use of modeling found that 71% of the population showed a high level in the development of creativity and 29% said a mid-level creative development; by this reason, is arrived to the conclusion of that through a planning adequate and leading to out activities specific, the use of the workshop of modeling of plasticine and masses, strengthened the development of the capacity creative.